FAKTOR DETERMINAN PERGERAKAN HARGA SAHAM ISLAMIC INDEKS PERIODE 2008 – 2018 - Dika Zanuar Virgantara; Eka Handriani (JURNAL STUDI MANAJEMEN ORGANISASI, 2020)
This study aims to determine the effect of EPS, NPM, DER, CR and PER on stock prices on the Jakarta Islamic Index (JII) for the period 2008-2018 listed on the Indonesia Stock Exchange. This type of research is causal associative research. The research population is 30 companies. The sampling technique is a purposive sampling technique and obtained a sample of 16 companies. Data analysis methods used are correlation, regression, determination, t test and F test. The results of the study show that partially EPS and NPM variables partially have a significant effect on stock prices, while DER, CR and PER variables partially have no significant effect and have a direction negative towards share prices on the Jakarta Islamic Index (JII) for the period 2008-2018 listed on the Indonesia Stock Exchange.